Spatial Correlation Increase in Single‐Sensor Satellite Data Reveals Loss of Amazon Rainforest Resilience - Lana L. Blaschke; Da Nian; Sebastian Bathiany; Maya Ben‐Yami; Taylor Smith; Chris A. Boulton; Niklas Boers (Earth's Future)
Abstract The Amazon rainforest (ARF) is threatened by deforestation and climate change, which could trigger a regime shift to a savanna‐like state. Whilst previous work has suggested that forest resilience has declined in recent decades, that work was based only on local resilience indicators, and moreover was potentially biased by the employed multi‐sensor and optical satellite data and undetected anthropogenic land‐use change. Here, we show that the average correlation between neighboring grid cells' vegetation time series, which is referred to as spatial correlation, provides a more robust resilience indicator than local estimations. We employ it to measure resilience changes in the ARF, based on single‐sensor Vegetation Optical Depth data under conservative exclusion of human activity. Our results show an overall loss of resilience until around 2019, which is especially pronounced in the southwestern and northern Amazon for the time period from 2002 to 2011. The results from the reliable spatial correlation indicator suggest that in particular the southwest of the ARF has experienced pronounced resilience loss over the last two decades.